Dietary variability in Middle Holocene South American shellmounds: Insights from isotopic analysis and an adapted Bayesian MixSIAR model - Marina Di Giusto; André Fumis; Murilo Bastos; Victor Fossaluza; Rafael Stern; Jéssica Mendes Cardoso; Estelle Herrscher; Klervia Jaouen; Veronica Wesolowski (PLoS ONE, 2025)
The degree of homogeneity in the diet of archaeological populations associated with Brazilian shellmounds ( sambaquis ) is an ongoing debate. Isotopic studies have the potential to document both intra- and inter-group dietary variability, especially when paired with quantitative tools, such as Bayesian Mixing Models. In this study, we investigate intra-site variability on diet at two shellmounds in southeastern Brazil: Piaçaguera (7151–5668 yBP), characterized by two distinct burial clusters, and Moraes (6791–5590 yBP). We analyzed δ 13 C and δ 15 N on human and fauna bone collagen ( n = 43) and on human dentine collagen ( n = 5 teeth). Our data were complemented by previously published isotopic data from these sites ( n = 88) and from other Brazilian shellmounds ( n = 51). To quantify the consumption of different food sources, we adapted the Bayesian MixSIAR model to integrate both bone and dentine values without compromising sample independence. Our results indicate that marine fish contributed approximately 30–50% to the diet of individuals from Piaçaguera, and terrestrial animals accounted for 16–45% of the diet of individuals from Moraes. We observed a slight difference in the consumption of marine and terrestrial sources between the burial groups in Piaçaguera and a higher intake of freshwater fish among subadults in Moraes. New radiocarbon dating in Piaçaguera indicates that the two burial groups did not belong to distinct chronological periods. These findings highlight the importance of a constant dialog between archaeological and isotopic data. The adapted MixSIAR model validated and increased the robustness of our results, proving to be effective in delineating dietary patterns in past groups from distinct archaeological contexts.